KINERJA KARYAWAN DAN PRODUKTIVITAS PERUM DAMRI - Prima Widiyanto; Damara Indra Wahyudi; Suparwan C.K (Institut Transportasi dan Logistik Trisakti, 2017)
Perum DAMRI is a company engaged in the service of people and goods transportation on the road, with the main task of carrying out land transportation by bus, truck, and other motorized vehicles.The problem in this thesis is how the image of Perum DAMRI employee performance, how productivity generated Perum DAMRI and how the influence of employee performance to productivity Perum DAMRI during period of year 2016. The writer used questionnaires data collection technique to 40 respondents and unstructured interview by using quantitative research method with simple linear regression test. The result of the research shows that the employee's performance is considered good by the respondent, the productivity is good by the respondent, and the result of T statistic test is 2.370 with significance value 0,023 <0,05 which means there is significant influence between employee performance with productivity and R2 test results show the magnitude of the effect of performance variables on productivity is 55.9% (close to 1) and can be said to have a strong relationship between the two variables. The conclusion is that the performance of DAMRI employees is said to be well proven with 41.5% of respondents giving answers Often, DAMRI productivity is said to be good with 44.5% of respondents giving answers Contributing, and there is influence between employee performance on productivity.